Principles and Practice of Recording Data in Toxicological Pathology - Naylor, D. C. (Methods of Information in Medicine, 1981)
A computer-assisted system for handling all data collected at autopsy and during the subsequent his-topathological examination of laboratory animals, used especially in chronic toxicity and carcinogenicity studies, is described. It is designed to be linked up to other systems used in toxicology so that data collected during toxicological, haematological and clinical-chemical examinations can be recalled by each pathologist. The system, while retaining its simplicity and flexibility, is a more refined version of one that was developed in another pharmaceutical company where it is still being used successfully. The present system is based on the Topography and Morphology Fields of the Systematized Nomenclature of Medicine (SNOMED); all morphological terms employed are carefully defined by the users, a factor contributing greatly to its success. Terminology is standardized, historical data can be recalled, and the system is able to comply with all other requirements of the regulatory authorities.
Keywords: Autopsy; Computer; Laboratory Animals; SNOMED; Toxicological Pathology